The Concept of Development of Ex-Mining C Mine in Wonosobo Regency - Zam Zam Masrurun; Wilda Rizkina Ulfa (Faculty of Engineering, Andi Djemma University, 2022)
The development of ex-mining land needs to be carried out to preserve the environment and make an alternative to sustainable, beneficial, and efficient use of ex-mining land. This study aims to provide an alternative concept for the development of ex-mining C excavation in Kertek District and Mojotengah District in Wonosobo Regency so that ex-mining land can still have economic value but is sustainable from the physical and environmental aspects. This research used a SWOT analysis technique. Data analysis was carried out from the results of collecting field facts and secondary data to identify existing conditions and ideal conditions to be achieved, as well as through alternative studies by identifying and analyzing segmentation based on land use, location, and existing conditions. The results of the study resulted in the concept of Eco-community Highland Tourism. This concept is to develop an area with high environmental quality and human resources, driven by the tourism sector as a priority. This concept contains the principles of improving environmental quality, economic sustainability, community empowerment, and the development of the tourism sector by the upland agricultural sector.